Layer-by-Layer Assembled Bacterial Cellulose/Graphene Oxide Hydrogels with Extremely Enhanced Mechanical Properties - Luo, Honglin; Dong, Jiaojiao; Yao, Fanglian; Yang, Zhiwei; Li, Wei; Wang, Jie; Xu, Xinhua; Hu, Jian; Wan, Yizao (Nano-Micro Letters, 2018)
Uniform dispersion of two-dimensional (2D) graphene materials in polymer matrices remains challenging. In this work, a novel layer-by-layer assembly strategy was developed to prepare a sophisticated nanostructure with highly dispersed 2D graphene oxide in a three-dimensional matrix consisting of one-dimensional bacterial cellulose (BC) nanofibers. This method is a breakthrough, with respect to the conventional static culture method for BC that involves multiple in situ layer-by-layer assembly steps at the interface between previously grown BC and the culture medium. In the as-prepared BC/GO nanocomposites, the GO nanosheets are mechanically bundled and chemically bonded with BC nanofibers via hydrogen bonding, forming an intriguing nanostructure. The sophisticated nanostructure of the BC/GO leads to greatly enhanced mechanical properties compared to those of bare BC. This strategy is versatile, facile, scalable, and can be promising for the development of high-performance BC-based nanocomposite hydrogels. Highlights: 1 A modified in situ static culture method (layer-by-layer assembly, LBLA) was developed. 2 The LBLA method ensures uniform distribution of graphene oxide (GO) in bacterial cellulose (BC) and makes very thick BC/GO hydrogels with homogeneous structures. 3 The BC/GO hydrogels show greatly enhanced mechanical properties over bare BC.